2013
DOI: 10.1111/acem.12165
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physicians Accurately Interpret Video Capsule Endoscopy Findings in Suspected Upper Gastrointestinal Hemorrhage: A Video Survey

Abstract: Background: Acute upper gastrointestinal (GI) hemorrhage is a common emergency department (ED) presentation whose severity ranges from benign to life-threatening and the best tool to risk stratify the disease is an upper endoscopy, either by scope or by capsule, a procedure performed almost exclusively by gastroenterologists. Unfortunately, on-call gastroenterology specialists are often unavailable, and emergency physicians (EPs) currently lack an alternative method to endoscopically visualize a suspected acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Training of ER physicians to interpret VCE images has also been found to be feasible in a survey study involving 126 emergency department physicians. 91 There are concerns about the costs of VCE used in such circumstances, but a cost-effectiveness analysis comparing VCE with other strategies for managing UGIB showed that VCE was cost-effective for patients at low and moderate risk presenting to the ER with UGIB. 92 …”
Section: Consensus Statementsmentioning
confidence: 99%
“…Training of ER physicians to interpret VCE images has also been found to be feasible in a survey study involving 126 emergency department physicians. 91 There are concerns about the costs of VCE used in such circumstances, but a cost-effectiveness analysis comparing VCE with other strategies for managing UGIB showed that VCE was cost-effective for patients at low and moderate risk presenting to the ER with UGIB. 92 …”
Section: Consensus Statementsmentioning
confidence: 99%
“…Poor visualisation of the duodenum due to the lapsed battery life of PillCam Eso was a major factor in lack of concordance between CE and OGD findings; this could potentially be addressed in newer generation capsules. ED physicians appeared to be competent to use the system after a brief training period [22]. Initial cost analyses appear favourable although further studies are required to validate this [20].…”
Section: Upper Gi Bleedingmentioning
confidence: 91%
“…Given the lack of reliable noninvasive diagnostic tools, the indication for emergency endoscopy is generally based on clinical parameters 2 3 4 . Novel tools that can determine presence or absence of severe bleeding may aid urgent triage and also save resources by avoiding unnecessary emergency endoscopies 5 . We present a prospective pilot trial, which aimed to evaluate feasibility and safety of detection of acute UGIB using a novel telemetric sensor capsule.…”
Section: Introductionmentioning
confidence: 99%